2023
DOI: 10.3389/fvets.2023.1163927
|View full text |Cite
|
Sign up to set email alerts
|

Teaching clinical hematology and leukocyte differentiation in veterinary medicine using virtual patients

Hannah Marahrens,
Matthias Gerhard Wagener,
Elisabeth Schaper
et al.

Abstract: Due to contact restrictions imposed because of the COVID-19 pandemic, we created a novel digital course on the Moodle learning platform for winter term in 2020. In the clinical pathology course (CPC) with hematological content, third-year students were able to work independently on 10 extra digital cases of internal medicine involving eight different animal species as a compensation for the reduction in traditional microscopy exercises. Each case presented was initiated using an anamnesis, also the participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…In addition, digital resources are persistent and therefore easy to use over longer periods of time ( 30 ). Some studies have also shown that blended learning with a mixture of digital and face-to-face teaching not only has a positive effect on motivation ( 28 , 37 ), but also on learning success ( 38 ) and students’ academic results ( 28 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, digital resources are persistent and therefore easy to use over longer periods of time ( 30 ). Some studies have also shown that blended learning with a mixture of digital and face-to-face teaching not only has a positive effect on motivation ( 28 , 37 ), but also on learning success ( 38 ) and students’ academic results ( 28 , 39 ).…”
Section: Discussionmentioning
confidence: 99%